TI_GERICHTE 52.2005.129 vom 25. Oktober 2005 , autorizzazzione per la costruzione di una casa e di una strada d'accesso - TI Tribunale d'appello (2005)
autorizzazzione per la costruzione di una casa e di una strada d'accesso